2015
DOI: 10.14800/nt.251
|View full text |Cite
|
Sign up to set email alerts
|

Central regulation of food intake in mammals and birds: a review

Abstract: Appetite regulates by a complex system of central and peripheral signals which interact in order to modulate ingestion response. A number of peptides comprise a complex network that regulates feeding behavior in vertebrates. This review is focused on the main neurotransmitters and peptides that influence feeding responses in mammals and birds. On the basis of literature review, there are several evidences that neurotransmitters have different effects on food intake between mammals and birds. Also, central regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…The dopamine concentration in the feed restricted group was higher than the ad libitum group. Our result may be supported by that previous finding that the intracerebroventricular injection of dopamine decreases food intake in chickens (37), and further confirms the association of dopamine with feed intake (22,23). One reason may be that feed restriction stimulates a greater state of excitement in the birds when feeding owing to their greater hunger.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The dopamine concentration in the feed restricted group was higher than the ad libitum group. Our result may be supported by that previous finding that the intracerebroventricular injection of dopamine decreases food intake in chickens (37), and further confirms the association of dopamine with feed intake (22,23). One reason may be that feed restriction stimulates a greater state of excitement in the birds when feeding owing to their greater hunger.…”
Section: Discussionsupporting
confidence: 91%
“…In chickens, it is additionally responsible for neuroplasticity (20) and altering dopaminergic components of the hippocampus (21). On the other hand, dopamine, a major catecholamine neurotransmitter in the central nervous system of mammals and birds, was known to be affected by learning ability, food intake behaviors, and feed restriction (22)(23)(24), and can modulate the hippocampal synaptic plasticity (25). That is, therefore, we think that dopamine may act in a role connecting behavior and neuron activity of hippocampal transcriptome in response to feed restriction.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that 5-HT hypophagia and hyperdipsia were mediated by different mechanisms in the central nervous system ( Zendehdel et al, 2012a ). It is showed that there is a neural interaction between serotonergic systems and melanocortin in terms of nutritional behavior in broilers ( Zendehdel and Hassanpour, 2014 ). The 5-HT affects the centers that regulate nutrition and energy balance ( Zendehdel et al, 2012b ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of food intake regulation has been well-demonstrated in mammals as food intake is a complex biological process, involving in both the peripheral and central nervous system (CNS) control mechanisms ( 4 ). Like in mammals, the CNS, specifically the hypothalamus, has emerged as a key site in appetite control for birds ( 5 ), and are potentially involved in the regulation of birds' feed intake under stress.…”
Section: Introductionmentioning
confidence: 99%